KARAKTERISTIK ISTRI DALAM UPAYA MENINGKATKAN PENDAPATAN RUMAH TANGGA NELAYAN TRADISIONAL DI DESA BULAWAN INDUK KECAMATAN KOTABUNAN KABUPATEN BOLAANG MONGONDOW TIMUR - Onibala, Gabriel; Sondakh, Srie J.; Durand, Swenekhe S. (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2019)
AbstractThe purpose of this study is to determine the characteristics of the wife in an effort to increase the income of traditional fishermen households in Bulawan Induk Village, Kotabunan District, Bolaang Mongondow Regency, East Sulawesi Province. Data collection was carried out on fishermen's wives and the contribution of traditional fishermen family income in Bulawan Induk Village, Kotabunan Subdistrict, Bolaang Mongondow Regency, North Sulawesi Province, by observation, interview and questionnaire. The data obtained were processed and analyzed descriptively. Descriptive analysis is intended to provide a discussion or interpretation of the data to obtain conclusions. Descriptive data analysis will provide a description of the information with sentences associated with existing theories, through simple calculations such as; addition, average and percentage. Research and discussion can be concluded, as follows: 1) the characteristics of the fishermen's wife, in this case the fisherman's wife, chooses to work because it helps support the family economy. most fishermen wives work at the age range of 51-60 because at this age the respondents of fishermen wives are wiser in taking initiatives to do work. However, education is not a major factor for work because in the work carried out by the fishermen's wives only attitudes and skills are needed in doing the work of the respondents of the fishermen's wives; 2) contributions can be seen from the various types of work done by fishermen's wives that is equal to 36.29% of the total family income of fishermen.Keywords: characteristics, fishermen's wife, contributions, Bulawan IndukÂ AbstrakPenelitian ini bertujuan untuk mengetahui karakteristik istri dalam upaya meningkatkan pendapatan rumah tangga nelayan tradisional di Desa Bulawan Induk Kecamatan Kotabunan Kabupaten Bolaang Mongondow Timur Provinsi Sulawesi Utara. Pengumpulan data dilakukan pada istri nelayan yangberkontribusi pend padaapatan keluarga nelayan tradisional dengan cara observasi, wawancara, dan kuisioner. Data dianalisis secara deskriptif dengan memberikan bahasan atau penafsiran terhadap data-data untuk memperoleh kesimpulan. Hasil penelitian menyatakan sebagai berikut : 1) karakteristik istri nelayan dalam hal ini istri nelayan tersebut, memilih bekerja karena untuk membantu menopang perekonomian keluarga. istri nelayan kebanyakan bekerja pada kisaran umur 51-60 karena pada umur dewasa ini responden istri nelayan lebih bijak dalam mengambil inisiatif untuk melakukan suatu pekerjaan. Namun pendidikan tidak menjadi faktor utama untuk bekerja karena dalam pekerjaan yang dilakukan oleh istri nelayan hanya diperlukan sikap dan keterampilan dalam melakukan pekerjaan responden istri nelayan; 2) kontribusi dapat dilihat dari berbagai jenis pekerjann yang dilakukan istri nelayan yaitu sebesar 36,29% dari total pendapatan keluarga nelayan.Kata kunci : karakteristik, istri nelayan, kontribusi, Bulawan Induk